BAZEX SYNDROME - A CASE REPORT - Hassan Iffat; Abid Keen; Mashkoor Ahmad; Qazi Masood (Our Dermatology Online, 2011)
Acrokeratosis paraneoplastica of Bazex is a rare but distinctive paraneoplastic dermatoses. This condition is a cutaneous marker of supra-diaphragmatic neoplasia. This syndrome is important because the cutaneous findings precede the onset of symptoms referable to the underlying neoplasm by several months in most of the cases.A 42 year old male who had scaly hyperkeratotic, papulosquamous lesions on face and dorsa of hands and feet with a suspicion of an underlying gastric neoplasm and a diagnosis of Bazex syndrome is being reported in view of the rarity of this condition.